ARABIC CONSERVATION METHODOLOGIES - Keyrouz, Bachir (European Scientific Journal, ESJ, 2014)
As confirmed by countless sites that were included in Unesco’s World Heritage List, the historical cities of the Arabic world represent precious witnesses of a unique urban legacy featuring distinct spiritual, social, economic and artistic expressions. Throughout centuries, the cultural traditions of Arabic societies were able to crystallize usually in permanent form. Individual monuments and, especially in complex urban structures, reflect particular modes of articulating space and of integrating visual art into architectural structures. Through such crystallization processes, a great variety of regional expressions of Arabic heritagehas been produced, translating the basic attitudes of a religion that put strong emphasis on ritualized forms of social conduct and individual behavior, but was also able to integrate local traditions responding to specific environmental factors with surviving pre-Arabic heritage leading to a Sustainable Arabic Legacy. It is within this wider cultural debate between utopia and nostalgia that we have to position the issue of historical cities and to search for solutions capable of maintaining and developing them as vibrant generators of meaningful civic life, rather than lifeless empty shells or mere economic assets in the service of modern tourism – a phenomenon that is largely fuelled by people’s frustration with the sterility of their modern urban environment. The concept of historical urban landscapes is not absolutely new as one finds traces of this new ideology partially expressed in theories and International documents dating back to the 1930’s as well. What is new and significant perhaps is the changed perception at the potential of this concept, of not treating these urban areas as static objects of admiration but as living spaces for sustainable communities (Rodwell, 2007). Some key points regarding Conservation of Historic Urban Landscapes are listed as follows: Conservation of material architectural culture retains its place even today but is augmented by enhancing the intangible cultural values by present adaptations and future transmissions; of not saving them as museum pieces but as living spaces, by understanding the fact that they undergo dynamic and continual changes, thus recognizing the change in value judgments; of protecting urban environments of which authentic and integrated character contributes to local and national identity, and on a broader scale to global heritage; of protecting their environmental character by giving due importance to their settings, endangered by natural and ecological factors or destructive human interventions; of protecting the socio-economic and cultural character of the associated communities by recognizing these values and by retaining and re-interpreting, enhancing and enriching them further; byrealizing that all economic, social, cultural and environmental assets/capitals of urban environments are finite resources; thus integrating and combining economic, social, cultural and environmental development aspects, thereby promoting sustainable Urban Architectural Conservation has thus moved on from preserving the present past to conserving the future.